The Territorial Distribution of Incidence with Urogenital Chlamydia, Gonorrhea, and their Associated Complications in the Russian Federation - A. A. Abramov (Эпидемиология и вакцинопрофилактика)
Relevance. Urogenital chlamydia is one of the most common sexually transmitted infections. Chlamydia often presents with minimal or no symptoms. However, it can be a major cause of pelvic inflammatory disease (PID), infertility, and ectopic pregnancy in women, as well as epididymitis, orchitis, and infertility in men. Aim. To study the territorial patterns of incidence of urogenital chlamydia, gonorrhea, and their associated complications in the Russian Federation in 2011 to 2019. Materials and methods. Official statistics on the incidence of urogenital chlamydia, gonorrhea, PID, female and male infertility in the Russian Federation were analyzed. Statistical analysis, graphing, table creation, data visualization, and research results analysis were conducted using Microsoft Excel 2010 and IBM SPSS Statistics 22 software. GIS mapping was performed using the GIS «Axioma». Results and discussion. From 2011 to 2019, the Russian Federation observed a decrease in the incidence of urogenital chlamydia, gonorrhea, and PID, while there was an increase in the incidence of male and female infertility. The geographical distribution remained stable, with areas characterized by consistently low and high incidence rates. A correlation was found between the incidence of urogenital chlamydia, gonorrhea, and their complications. The association between gonorrhea and PID was found to be more significant than the association between chlamydia and PID, possibly due to the higher risk of complications associated with gonorrhea. However, no correlation was found between gonorrhea and infertility, possibly because this complication manifests with a time delay and has multifactorial causes. Conclusions. Based on the presented data, it can be concluded that the incidence of urogenital chlamydia and gonorrhea affects the frequency of male and female infertility. Therefore, the implementation of screening examinations for sexually active individuals of reproductive age using appropriate laboratory diagnostic methods, along with the development of preventive measures for sexually transmitted infections, including urogenital chlamydia, is justified and should be widely practiced.